SCIENTIFIC STRENGTHENING ACTIONS AS A MEANS OF CONTROLLING ANTIMICROBIAL RESISTANCE IN THE CONTEXT OF SDG 12.A - Morais, Vinicius Cavalcante; Claudino, Brena Freire de Oliveira; dos Santos, Ana Beatriz Rodrigues; Macedo, Ana Beatriz Batista Maia; Gomes, Cleyton de Sousa; da Silva, Roosewelt Andriel Barbosa; Vieira, Mateus Mendes; de Lima, Kaíque Yago Gervazio; Vasconcelos, Ulrich (Seven Editora, 2025)
Microbial resistance to conventional therapy antibiotics (RAM) is one of the two biggest challenges of the 21st century. From different years, the beginning of the present series marks a definition of an important agenda for human development. Two 17 objectives, the one that deals with development brings together a series of goals that converge as the theme “microbial resistance”. Goal 12.4 deals with technological development, strengthened by scientific promotion and partnership between nations. This text presents an analysis of the topic, pointing out the intimate relations between the technical-scientific development with the crisis of two antibiotics, proposing a discussion on how this scenario can contribute to the reduction of deaths due to microbial infections. The text was produced by Master and Doctorate students of two Post-Graduation programs, as part of the final exercise of the discipline that deals with this topic. DOI: https://doi.org/10.56238/sevened2025.036-048